Arab Countries in Transition : Economic Outlook and Key Challenges. (Policy Papers; Policy Paper ;, 2015)
The Arab Countries in Transition (ACTs) have had diverging trajectories over the past year and face an uncertain outlook.1 Improvements in the European economy, lower oil prices, and some progress on the policy front have provided tailwinds to growth, which is expected to pick up significantly in Egypt and Morocco. At the same time, unemployment remains high. Moreover, several of the ACTs have also suffered from intensifying and spreading conflicts that cause widespread human suffering and sizeable economic challenges. Libya and Yemen are directly affected, while spillovers from these conflicts and the civil wars in Iraq and Syria weigh on Jordan and Tunisia, as well as other countries in the region (e.g., Lebanon, Djibouti), Turkey and Europe. These spillovers come most prominently in the form of large refugee flows, deteriorating security, and pressures on economic infrastructures and labor markets. All these factors add urgency to the need in the Arab countries to strengthen economic resilience and address long-standing sources of inequity and exclusion. Coordinated and scaled-up support from the international community will be also critical in stabilizing conditions in the region, addressing the refugee crisis, and securing a more promising economic future for the ACTs in this challenging environment.